Farming Systems to Enhance Micronutrient Absorption in Crops - Edi Wiraguna (Research Highlights in Science and Technology Vol. 2, 2023)
Micronutrients are essential for the human body. The low content of micronutrients in meals can result in malnutrition. Therefore, the production of crops containing micronutrients is important. This study aims to discuss essential micronutrients and increase the availability of micronutrients to edible parts, including grains and leaves. Essential micronutrients for humans are Zn (zinc) and Fe (iron) because iron deficiency can result in anemia, poor health during pregnancy, and decreased immune function. Zinc is essential for plant growth and development, and a low concentration of zinc can result in leaf necrosis. Foliar application and abundance of microbial in soil are suggested to increase the availability of micronutrients to the crops and edible parts of crops. The foliar application raises the micronutrient content in edible parts because of its accessibility to transport the micronutrients from leaves to grains or other plant tissue. Foliar application can help crops to recover from leaf necrosis. Microbes in the soils, such as Acinetobacter and Rhizobium leguminosarum, can increase iron availability, so crops do not show the symptoms of iron deficiency. Other approaches, such as manure and slow-release fertiliser, can be suggested to increase micronutrient availability in crops.